Sistem Pengisian Baterei Menggunakan Buck Konverter - Elsi Martha; Asnil Asnil; Fivia Eliza (Universitas Negeri Padang, 2018)
This paper discusses the use of buck converter for battery charging using solar power sources. The nominal voltage of the battery used is 12 Volt and the output voltage of the solar panel without load is 22.68 Volts. Buck converter is used to reduce the output voltage of the solar panel and to control the stability of the output voltage is used Atmega 8 microcontroller. From the test results, the buck converter output voltage is stable at a value of 14.4 volts even though the input voltage is changed. Apart from that, the duration of battery charging is very much determined by weather changes that affect the ability of solar panels to produce energy for battery charging